2023
DOI: 10.1039/d3md00291h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and computational studies of piperidine/piperazine-based compounds endowed with sigma receptor affinity

Abstract: Herein, we describe our efforts to identify sigma receptor 1 (S1R) ligands through a screening campaign on our in-house collection of piperidine/piperazine-based compounds. Our investigations led to the discovery of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 37 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…To achieve this purpose, we overlapped the pharmacophore model with our previously reported lead compound 2-[4-(benzyl)-1-piperidin-1-yl]-1−4-(4-phenylpiperazin-1-yl)ethanone (1) having high affinity toward S1R (K i value of 3.2 nM). 20 The pharmacophoric alignment (Table 3) revealed that the benzyl group matched well with the hydrophobic feature; moreover, the model suggested that smaller groups might replace the benzyl moiety. To further investigate the performance of our model, we examined the pharmacophoric alignment for the analog compound 3-[4-[(4-fluorophenyl)methyl]-1-piperidyl]-1-[4-(4-hydroxyphenyl)piperazin-1-yl]propan-1-one (2) having a poor S1R affinity (K i value of 434.5 nM) 20 when compared to the analog compound 1 (see Table 3).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…To achieve this purpose, we overlapped the pharmacophore model with our previously reported lead compound 2-[4-(benzyl)-1-piperidin-1-yl]-1−4-(4-phenylpiperazin-1-yl)ethanone (1) having high affinity toward S1R (K i value of 3.2 nM). 20 The pharmacophoric alignment (Table 3) revealed that the benzyl group matched well with the hydrophobic feature; moreover, the model suggested that smaller groups might replace the benzyl moiety. To further investigate the performance of our model, we examined the pharmacophoric alignment for the analog compound 3-[4-[(4-fluorophenyl)methyl]-1-piperidyl]-1-[4-(4-hydroxyphenyl)piperazin-1-yl]propan-1-one (2) having a poor S1R affinity (K i value of 434.5 nM) 20 when compared to the analog compound 1 (see Table 3).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Finally, we carried out in vitro assays to test the affinity of 3-6 against S1R following a previously reported procedure. 20 Compounds 3−6 showed K i values ranging from 4.38 to 25.4 nM (Table 3), thus demonstrating good affinity when compared to reference compound haloperidol (K i value of 2.6 nM). 20 Notably, experimental data confirmed previous in silico results in terms of pharmacophoric performance for the design of new potential S1R ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 3 more Smart Citations